Origin of intramuscular nerve action potential. Issue 12 (December 1987) - Gutmann, L; Hopf, H C; Roeder, R
Abstract : The origin of the intramuscular nerve action potential (INAP) was investigated using conventional surface recording electrodes. The appearance of the INAP was (1) associated with subjective paresthesias, (2) recorded only when the reference electrode (G2) was over an appropriate digital nerve, (3) increased in latency as G2 was placed more distally, (4) blocked by an orthodromic sensory nerve action potential arising from the thumb, and (5) abolished with an anaesthetic block in the digital nerve proximal to G2. The findings indicate that the INAP is recorded by the G2 electrode from the digital nerve.